Предмет: Математика,
автор: allasnovedskay
решите -12+х= -11 -(-10) . х+(-18)= -29-(-19) . -16-х=32-(-12)
Ответы
Автор ответа:
0
-12+х= -11 -(-10)
-12+х=-1
х=-1+12
х=11
х+(-18)= -29-(-19)
х-18=-10
х=-10+18
х=8
-16-х=32-(-12)
-16-х=44
-х=44+16
-х=60
-12+х=-1
х=-1+12
х=11
х+(-18)= -29-(-19)
х-18=-10
х=-10+18
х=8
-16-х=32-(-12)
-16-х=44
-х=44+16
-х=60
Автор ответа:
0
х+(-18)= -29-(-19)
Автор ответа:
0
мне нада была это ещё вчера но всё равно спасибо большое
Похожие вопросы
Предмет: Английский язык,
автор: veselevaevgenia
Предмет: Химия,
автор: Аноним
Предмет: Алгебра,
автор: vladsoshin123
Предмет: География,
автор: coolmyc